Insect-specific virus evolution and potential effects on vector competence - Öhlund, Pontus; Lundén, Hanna; Blomström, Anne-Lie (Virus genes, 2019)
The advancement in high-throughput sequencing technology and bioinformatics tools has spurred a new age of viral discovery. Arthropods is the largest group of animals and has shown to be a major reservoir of different viruses, including a group known as insect-specific viruses (ISVs). The majority of known ISVs have been isolated from mosquitoes and shown to belong to viral families associated with animal arbovirus pathogens, such as Flaviviridae, Togaviridae and Phenuiviridae . These insect-specific viruses have a strict tropism and are unable to replicate in vertebrate cells, these properties are interesting for many reasons. One is that these viruses could potentially be utilised as biocontrol agents using a similar strategy as for Wolbachia . Mosquitoes infected with the viral agent could have inferior vectorial capacity of arboviruses resulting in a decrease of circulating arboviruses of public health importance. Moreover, insect-specific viruses are thought to be ancestral to arboviruses and could be used to study the evolution of the switch from single-host to dual-host. In this review, we discuss new discoveries and hypothesis in the field of arboviruses and insect-specific viruses.